A new pore-scale capillary pressure model for fractional wettability media using cylindrical mixed-wet tubes. (July 2021) - Zheng, Jun; Liu, Hongbo; Liu, Ning; Xiao, Yihang
Highlights: A cylindrical mixed-wet tube displays either piston-like or stepwise displacement. The capillary entry pressures in mixed-wet pores are numerically calculated and approximately formulated. A FW medium features a same pore displacement pattern and a fixed displacement sequence. The proposed model demonstrated reliable prediction capability and can be used in various wettability conditions. Abstract: The capillary-pressure/saturation relationship is a key property for modeling multiphase flow in fractional-wet (FW) porous media. However, the multiphase flow mechanism in such media has not been clearly understood yet and few capillary pressure models have been developed or verified for the range of wettability conditions that often occur in natural subsurface. This work presents a new general pore-network capillary pressure model for FW media. The pore-network is the first to adopt cylindrical mixed-wet pores and follows truncated Weibull pore size distribution. The pore level displacements of the mixed-wet pores including a new stepwise scenario are investigated by using the MS-P method and employed in the model. We simulate a primary drainage process with sequentially increased capillary pressure. Each individual pore is tested for invasion at a given capillary pressure ( P c ) when ignoring the pore connectivity, then the water saturation ( S w ) is calculated by integrating all pore elements to yield the P c / S w relation. The model can simulate capillary pressure curves for FW media in various wettability conditions. The underlying multiphase flow mechanisms for FW media have been well revealed and clarified with the model. Three sets of published experimental data with different wettability conditions are successfully predicted for the model validation. Comparisons with extant models are performed to prove the improvement and generality. This new model is an extension to the conventional uniform-wet capillary pressure theory, as it is consistent when the fraction of the oil-wet surface is either equal to zero or one. Graphical abstract: Pore level displacements of a cylindrical mixed-wet tube including a new stepwise scenario are first investigated and employed in the new model. The underlying multiphase flow mechanisms of capillary pressure curve of FW media have been well revealed and clarified with the pore-scale model. Image, graphical abstract